Self-Efficacy Analysis For Students To Foster Entrepreneurial Interest In The Agricultural Sector - Ridha Rizki Novanda (Cita konsultindo, 2023)
There was a substantial relationship between self-efficacy and student entrepreneurship interest, which was consistent with theory, opinion, and prior research. So it is important to analyze self-efficacy analysis for students to foster entrepreneurial interest in the agricultural sector. By sending 100 questionnaires online, the study was carried out in Indonesia. In Indonesia, students with agricultural backgrounds were initially screened with the requirement that they have taken entrepreneurial courses. A type of research called descriptive quantitative research describes the data that has been collected exactly as it is and then analyzes itBased on the results of the analysis, self -efficacy students in running a business in the agricultural sector have high criteria on the occasion to start a new business by identifying opportunities, creating something differentiating by identifying opportunities, developing a business by evalating existing opportunities, develops skills by evaluating existing opportunities, Operate a new business, utilize a new business, leadership structure in entrepreneurship organizations, and mechanism in entrepreneurship organizations.